Acute peripheral catecholaminergic changes in rat after MPTP and MPP+ treatment (Revista Española de Fisiología, 1989)
The effects of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and its main metabolite 1-methyl-4-phenylpyridinium ion (MPP+) on the peripheral catecholaminergic system of the rat were investigated.MPTP and MPP+ injections (20 mg/kg i.p.) caused a marked acute depletion of heart noradrenaline, up to 75% twelve hours after the administration, and a decrease of adrenal gland adrenaline.The time-course of the effect of MPTP and MPP+ is reported, together with a decrease in the tyrosine hydroxylase activity after MPTP treatment, more evident in the adrenal glands.Pargyline (50 mg/kg i.p.) is not able to prevent such a neurotoxic peripheral effect.